2012
DOI: 10.1002/adsc.201100463
|View full text |Cite
|
Sign up to set email alerts
|

Reductive Reformatsky–Honda Reaction of α,β‐Unsaturated Esters: Facile Formation of 1,3‐Dicarbonyl Compounds and β‐Hydroxy Esters

Abstract: The reaction of tris(triphenylphosphine)-with diethylzinc (Et 2 Zn) easily afforded a rhodium-hydride complex that effects the 1,4-reduction of a,b-unsaturated esters to give rhodium enolates. Formation of the rhodium enolate is followed by transmetalation with the zinc species to give a Reformatsky-type reagent, and this reacts with various acid chlorides at the aposition to give b-keto esters. The Reformatsky-type reagent also reacts with various electrophiles such as aldehydes, ketones and acid anhydrides t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
16
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 48 publications
(8 reference statements)
1
16
0
Order By: Relevance
“…However, this result confirmed that the approach would provide a promising route to such a cyclic compound, because a number of studies have reported on the enantioselective reductive aldol cyclization. 13,25,26) On the basis of previous results and various examinations of reaction conditions, 20,21) we proposed the following mechanism (Fig. 2).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…However, this result confirmed that the approach would provide a promising route to such a cyclic compound, because a number of studies have reported on the enantioselective reductive aldol cyclization. 13,25,26) On the basis of previous results and various examinations of reaction conditions, 20,21) we proposed the following mechanism (Fig. 2).…”
Section: Resultsmentioning
confidence: 99%
“…Methyl 3-Hydroxy-2-methyl-3-phenylpropanoate (3a) 20,21) Each diastereomers of the title product (3a) were purified by column chromatography (AcOEt : hexane=2 : 3) and were obtained in 40% (39 mg; syn form) and 55% 20,21) Each diastereomers of the title product (3b) were purified by column chromatography (AcOEt : hexane=1 : 4) and were obtained in 36% (47 mg; syn form) and 48% yield (62 mg; anti form), respectively.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations